Magnetostratigraphy and Paleoenvironments of the Kuntila Lake Sediments, Southern Israel: Implications for Late Cenozoic Climate Variability at the Northern Fringe of the Saharo-Arabian Desert Belt - Larrasoaña, Juan Cruz; Waldmann, Nicolas; Mischke, Steffen; Avni, Yoav; Ginat, Hanan (Frontiers in Earth Science, 2020)
Abstract. The Negev Desert in southern Israel hosts a number of late Cenozoic lacustrine and palustrine sedimentary sequences that attest for past wetter conditions in what today constitutes one of the driest deserts on Earth. These sequences are of special importance because the Negev Desert forms part of the Levantine Corridor, which was probably the only continental bridge that enabled initial out-of-Africa expansion of our genus Homo.Yet, the paleoclimatic significance of these sequences still remains unknown, mainly due to their uncertain (late Pliocene to early Pleistocene) age. Here we present a combined sedimentologic, paleontologic and magnetostratigraphic study of one of these sedimentary sequences, the so-called Kuntila Lake sediments, which was carried out at the 30 m-thick Kuntila Gate section in the Nahal Paran basin, southern Israel.Sedimentological evidence and ostracod faunas indicate that these sediments accumulated in a long-lasting lacustrine basin that underwent periodic lake-level variations. Magnetostratigraphic measurements enable the recognition of a normal (N1) and a reverse (R1) polarity zones in the lower and upper halves, respectively, of the Kuntila Gate section. Correlation of N1 to the Olduvai Subchron (1.778 and 1.945 Ma) appears as the most likely option in view of previously published 10 Be ages derived for the uppermost part of the Kuntila Member in nearby sections. The large errors associated with these ages, however, suggest that correlation of N1 to Subchron C2An.1n (2.582-3.032 Ma) is also possible. Although our results do not resolve the age of the Arava Formation, they unequivocally relate the Kuntila Lake sediments with a long period of enhanced climatic variability because the tops of both subchrons are associated with 400 kyr eccentricity maxima. The inferred wetter conditions in the Negev Desert concurred, regardless of the age correlation, with periods of lake expansion in East Africa and clusters of short-lived expansions of the savannah throughout much of the Sahara. This would have led to the biogeographic connection between Africa and Eurasia, greening the path for the initial out-of-Africa dispersal of Homo. Further research on the Kuntila Lake sediments will be necessary to better determine the timing, extent and significance of such biogeographic connection.